2004
DOI: 10.1093/abbs/36.5.375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Stress and Phenytoin on the Long-term Potentiation (LTP) in Rat Hippocampal CA1 Region

Abstract: To investigate the changes of LTP in hippocampal CA1 region induced by chronic stress and the effect of phenytoin on them, thirty-two adult male Sprague-Dawley rats were randomly divided equally into four groups: control group, control-phenytoin group, stress-saline group and stress-phenytoin group. Isolated hippocampal slices of rats were used to observe the changes of long-term potentiation (LTP) in hippocampal CA1 field using electrophysiological technique. Amplitude of population spike (PS) and field excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Irrespective of the models that have been used, chronic overexposure to stress hormones has generally been found to reduce the ability to induce or maintain LTP and to enhance the likelihood to induce LTD, even when circulating corticosteroid levels at the time of recording were very low. This was observed for projections to the (dorsal) hippocampal CA1 area (Bodnoff et al, 1995;Gerges et al, 2001;Von Frijtag et al, 2001;Alfarez et al, 2003;Zheng et al, 2004;Aleisa et al, 2006a,b,c;Artola et al, 2006;Krugers et al, 2006;Holderbach et al, 2007;Ma et al, 2007;Srivareerat et al, 2009;Kamal et al, 2010;Sterlemann et al, 2010;Tran et al, 2011), the CA3 area (Kole et al, 2002(Kole et al, , 2004Pavlides et al, 2002;Maggio and Segal, 2011), the PFC (Cerqueira et al, 2007;Goldwater et al, 2009;Lee and Goto, 2011;Lee et al, 2011b;Quan et al, 2011a,b;Zhang et al, 2011), and the bed nucleus stria terminalis (Conrad et al, 2011). The reverse, however, was seen in the ventral-most part of the hippocampus (Maggio and Segal, 2011).…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Irrespective of the models that have been used, chronic overexposure to stress hormones has generally been found to reduce the ability to induce or maintain LTP and to enhance the likelihood to induce LTD, even when circulating corticosteroid levels at the time of recording were very low. This was observed for projections to the (dorsal) hippocampal CA1 area (Bodnoff et al, 1995;Gerges et al, 2001;Von Frijtag et al, 2001;Alfarez et al, 2003;Zheng et al, 2004;Aleisa et al, 2006a,b,c;Artola et al, 2006;Krugers et al, 2006;Holderbach et al, 2007;Ma et al, 2007;Srivareerat et al, 2009;Kamal et al, 2010;Sterlemann et al, 2010;Tran et al, 2011), the CA3 area (Kole et al, 2002(Kole et al, , 2004Pavlides et al, 2002;Maggio and Segal, 2011), the PFC (Cerqueira et al, 2007;Goldwater et al, 2009;Lee and Goto, 2011;Lee et al, 2011b;Quan et al, 2011a,b;Zhang et al, 2011), and the bed nucleus stria terminalis (Conrad et al, 2011). The reverse, however, was seen in the ventral-most part of the hippocampus (Maggio and Segal, 2011).…”
mentioning
confidence: 94%
“…Some 922 of the above-mentioned studies demonstrated that particular molecules are critical for the electrophysiological changes to occur, such as calcineurin and Ca 2ϩ /calmodulin-dependent protein kinase II (Aleisa et al, 2006a,b,c), NR2B subunits, inhibitor of nuclear factor-B (Christoffel et al, 2011), and brain-derived neurotrophic factor (Zhou et al, 2000;Radecki et al, 2005;Aleisa et al, 2006c). Compounds that prevented or normalized the development of changes in neural activity include nicotine (Aleisa et al, 2006a,b,c), antidepressants (Von Frijtag et al, 2001;Kole et al, 2002Kole et al, , 2004Kessal et al, 2006;Holderbach et al, 2007;Wang et al, 2010;Holm et al, 2011), ketamine (Li et al, 2011), memantine (Quan et al, 2011), antiglucocorticoids Karst and Joëls, 2007;Spyrka and Hess, 2010), and phenytoin (Zheng et al, 2004), whereas ␤-amyloid exacerbated the effects of chronic stress (Srivareerat et al, 2009;Tran et al, 2011). However, it is unclear whether these compounds 1) directly interfere with chronic-stress-dependent signaling pathways, 2) tap indirectly into the same pathways, or 3) compensate for/ counteract the effects of chronic stress through independent mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Valproic acid (VPA) had shown efficacy against spontaneous seizures and deficits in visuospatial learning in KA models when given at the chronic phase to KA but not pilocarpine models (Pitkanen and Kubova, 2004). Carbamazepine (CBZ) and phenytoin (PHT) but not ethosuximide (ETS) had shown efficacy against spontaneous seizures when administered at the chronic phase in pilocarpine model (Watanabe et al, 1992;Ambrosio et al, 2000;Zhang et al, 2004b). Topiramate (TPM) showed the ability to protect hippocampal mitochondria against an external Ca ++ challenge (in CA1 and CA3 pyramidal subfields) when given at the chronic phase.…”
Section: The Anticonvulsant and Neuroprotective Potentials Of Antiepimentioning
confidence: 99%
“…It is used as prophylaxis after brain injury [Hernandez, 1997]. Phenytoin prevented stress-induced reductions in CA3 apical dendritic length and branch point numbers [Watanabe et al, 1992] and prevented stress-induced LTP blockade [Zhang et al, 2004]. PHT may however induce brain injury through peroxidation of neuronal membrane lipids initiated by free radical-generating mechanisms [Willmore and Triggs, 1984].…”
Section: Phenytoin (Pht)mentioning
confidence: 99%